EFFORTS TO IMPROVE EARLY READING ABILITY THROUGH THE SYLLABIC METHOD AT SDN II KUDU - Juan Febri Adi Prayogo; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This study aims to determine whether the syllable method can improve the ability of grade I students at SDN II Kudu in reading the beginning and how much the resulting improvement is. This study uses a classroom action research method with a Kurt Lewin research design. Data collection techniques used are interviews, oral tests, documentation, and observation. The data collected was then analyzed descriptively quantitatively. The results showed that the syllable method could improve at the same time there was an increase in the initial reading ability of the first graders of SDN II Kudu. Judging from the increase in learning outcomes from the pre-cycle stage with an average value of 51.56 and classical learning completeness of 54.2% and the results of observing student learning activities of 75%. This increased in the first cycle, namely the average value of 80.83 with classical learning completeness of 79.2% and the results of student learning activity observation sheets of 90%. In the second cycle, it increased again with the percentage of students' average scores being 88.75 with students' classical learning completeness of 87.5 and the results of the student learning activity observation sheets being 100% in the very active category.